Cultivation of Diatom Skeletonema costatum in Airlift Photobioreactors - มงคลสิทธิ์ ศรัญญา; เผ่าทองศุข สรวิศ; ภวสันต์ ประเสริฐ (KKU Science Journal, 2012)
This work investigated the cultivation of Skeletonema costatum in a 3L airlift photobioreactor which was operated at superficial air velocity of 1.5 cm s-1, light intensity of 33.78 mmol photon m-2 s-1 with an initial cell density of 0.4 x 106 cell mL-1. The cultivation in a standard Guillard F/2 medium provided the final culture with a maximum cell density of 1.96 x 106 cell mL-1 at a specific growth rate of 0.032 h-1. Experimental findings reveal that a 4 fold increase in silica concentration in the standard Guillard F/2 medium could significantly increase the cell growth with a final cell density of 4.6 x 106 cell mL-1 at a specific growth rate of 0.046 h-1.